2022
DOI: 10.3389/fgene.2022.987519
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T polymorphism and cerebrovascular lesions in elderly patients with CSVD: A correlation analysis

Abstract: Plasma homocysteine (Hcy) has been identified as a potential risk factor for cerebral small vessel disease. Cerebral small vessel disease (CSVD) leads to cognitive impairment, depression, and other symptoms and is a common disease in middle-aged and elderly people. To investigate the relationship between 5,10-methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and CSVD in elderly patients, plasma levels of homocysteine (Hcy) and MTHFR genotyping were assessed. MRI and MRA were performed at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The linkage between the MTHFR gene and elevated homocysteine levels has been widely acknowledged, and the relationship between genetically-mediated HHcy and cerebrovascular diseases represented a major focus of current clinical research ( Li et al, 2022 ). The MTHFR C677T mutation included three polymorphisms (wild-type CC, heterozygous CT, and homozygous TT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linkage between the MTHFR gene and elevated homocysteine levels has been widely acknowledged, and the relationship between genetically-mediated HHcy and cerebrovascular diseases represented a major focus of current clinical research ( Li et al, 2022 ). The MTHFR C677T mutation included three polymorphisms (wild-type CC, heterozygous CT, and homozygous TT).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, homocysteine levels are susceptible to various external factors, including lifestyle and environmental influences, making it an unstable marker for early detection. Recent studies have indicated that the TT genotype is an independent risk factor for WMH ( Li et al, 2022 ). A meta-analysis of 36 prospective studies demonstrated that WMH is associated with increased risk of cognitive impairment, serving as a neuroimaging marker for dementia ( Hu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 23 ). However, as we mentioned above, applying only Cox regression analysis was inadequate and would overestimate the risk of cancer-specific death, because aside from the primary tumor, there were other factors that might threaten their life ( 24 ), and death due to other causes actually acted as a competing event to death caused by MBC. In this study, two nomograms were constructed to predict the survival probability of MBC patients based on the Fine and Gray competing risk analysis and multivariate Cox regression, respectively, to correct this bias.…”
Section: Discussionmentioning
confidence: 99%
“…A total of nineteen articles were included and 6941 hepatocellular carcinoma patients and 9436 healthy controls were enrolled [13,29,[32][33][34][43][44][45][46][47][48][49][50][51][52][53][54][55][56] (The flow chat of literature selection was showed in Figure 1 and Table S1 (see Table S1, Supplemental Digital Content, which showed the flow chat of literature selection, http://links.lww.com/MD/G441). The characteristics of the included studies were showed in Table 1.…”
Section: The Characteristics Of the Included Studiesmentioning
confidence: 99%